2004
DOI: 10.4049/jimmunol.172.3.1711
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Production of Proinflammatory Cytokines and Host Resistance to Acute Infection withTrypanosoma cruziin Mice Lacking Functional Myeloid Differentiation Factor 88

Abstract: Studies performed in vitro suggest that activation of Toll-like receptors (TLRs) by parasite-derived molecules may initiate inflammatory responses and host innate defense mechanisms against Trypanosoma cruzi. Here, we evaluated the impact of TLR2 and myeloid differentiation factor 88 (MyD88) deficiencies in host resistance to infection with T. cruzi. Our results show that macrophages derived from TLR2 −/− and MyD88−/− mice are less responsive to GPI-mucin derived from T. cruzi trypomastigotes and parasites. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
192
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(205 citation statements)
references
References 53 publications
7
192
1
2
Order By: Relevance
“…Several recent reports have explored the defective host defense and inflammatory response to several pathogens in MyD88-deficient mice, including S. aureus, L. monocytogenes, T. gondii, M. tuberculosis, and Trypanosoma cruzi (33)(34)(35)(36)(37)53). Similar to the results presented here, these studies demonstrated increased susceptibility to infection evidenced by an inability of MyD88-deficient mice to control pathogen levels.…”
Section: Discussionsupporting
confidence: 80%
“…Several recent reports have explored the defective host defense and inflammatory response to several pathogens in MyD88-deficient mice, including S. aureus, L. monocytogenes, T. gondii, M. tuberculosis, and Trypanosoma cruzi (33)(34)(35)(36)(37)53). Similar to the results presented here, these studies demonstrated increased susceptibility to infection evidenced by an inability of MyD88-deficient mice to control pathogen levels.…”
Section: Discussionsupporting
confidence: 80%
“…In Toxoplasma gondi-, Trypanosoma cruzi-and Leishmania major-infected MyD88 -/-mice, the absence of IFN-c production by primed lymphocytes upon recall with the respective antigen correlated with the failure of APC to produce IL-12 upon co-incubation with protozoan antigens [36][37][38][39]. In a recent study, IL-12 and TNF-a production by DC when co-incubated with whole S.…”
Section: Discussionmentioning
confidence: 94%
“…Most TLRs, upon recognition of discrete pathogen-associated molecular patterns, activate a set of adaptor proteins (e.g. myeloid differentiation protein 88 (MyD88)) leading to the nuclear translocation of transcription factors, such as NF-B and AP-1, and thus transcriptionally regulate host-cell responses to pathogens, including parasites (3)(4)(5). TLRs may also recognize endogenous ligands induced during the inflammatory response (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…Evidence is accumulating that the signaling pathways associated with TLRs not only mediate host innate immunity but are also important to adaptive immune responses to microbial infection (6). Epithelial cells express TLRs and activation of TLRs triggers an array of epithelial defense responses, including production and release of cytokines/chemokines and anti-microbial peptides (1)(2)(3)(4)(5)(6)(7)(8). Expression of TLRs by epithelia is tightly regulated, reflecting the specific microenvironment and function of each epithelial cell type.…”
mentioning
confidence: 99%